An introduction to Catholic social thought - Hornsby-Smith, Michael P. (Cambridge, UK ; New York : Cambridge University Press, 2006)
Michael Hornsby-Smith offers a critical introduction to Catholic social thought. While drawing on official papal and episcopal teaching, he takes seriously the need for dialogue with secular thought. He deliberates the social reality of injustices, providing analysis of their causes and suggesting appropriate social action responses.
Cover; Half-title; Title; Copyright; Contents; Tables and figure; Acknowledgements; Dedication; Abbreviations and acronyms; VATICAN COUNCIL DOCUMENTS ETC; PAPAL ENCYCLICAL SETC; CHAPTER 1 Introduction; CHAPTER 2 Capitalism in a global context; CHAPTER 3 The kingdom of God; CHAPTER 4 Christian citizenship; CHAPTER 5 Catholic social thought; CHAPTER 6 Human rights; CHAPTER 7 The family; CHAPTER 8 Economic life; CHAPTER 9 Social exclusion; CHAPTER 10 Authentic development; CHAPTER 11 War and peace; CHAPTER 12 Catholic responses to injustices; Appendix: Selected campaigning organizations.
Includes bibliographical references (pages 346-363) and index.
Print version record.
Keywords: Christian sociology -- Catholic Church; Church and social problems -- Catholic Church; Christian sociology -- Catholic Church; Church and social problems -- Catholic Church; RELIGION -- Christianity -- General; RELIGION -- Christian Life -- Social Issues; Christian sociology -- Catholic Church; Church and social problems -- Catholic Church; Electronic books